Accelerated Progress in Higher Education STEM Learning via Enhanced Practical Sessions - Tamás Kovács (Advanced Journal of STEM Education, 2026)
Higher education (HE) provides insight into learners’ future career paths and therefore plays a key role in shaping society. High-quality, professional teaching and learning strategies shape students' future orientations and interests. Students are entitled to the best possible delivery of HE modules and support from providers. This should include not only motivated and motivating tutors and practitioners but also engaging strategies and the integration of theory and practice. In practical STEM (Science, Engineering, Technology, and Mathematics) subjects, the practicals should be planned to bring students closer to their careers through everyday situations and easily digestible scenarios. This could be enhanced by involving students in academic or even educational research. An original concept to extend this approach is the Authentic-Digital Nexus (ADN) Framework. This framework is designed to bridge the gap between theoretical knowledge and real-world application in HE by strategically integrating authentic, problem-based learning with flexible, technology-enhanced delivery methods. The available modern technology allows practitioners to deliver even practical-based sessions remotely, and, as experience suggests, this fades the fear of the difference between face-to-face and remote delivery that has arisen in many cases since the Covid-19 pandemic lockdown. The proposed intervention involves a curriculum redesign within specific STEM modules, structured around the ADN framework.